Investigation of the effect of ocean acidification on the haemocyte proteome of the South African abalone, Haliotis midae - Carroll,SarahLeigh (Department of Molecular and Cell Biology, 2022)
Haliotis midae is an economically important marine invertebrate that is farmed in South Africa, contributing more than half of the revenue generated by the aquaculture industry. However, the future sustainability of abalone farming in South Africa is threatened by the ongoing climate crisis. The effect of climate change is unrelenting for organisms such as abalone, which rely on a succinct balance of physico-chemical environmental properties. Indeed, the ocean environment is susceptible to these imbalances and has already witnessed changes in seawater temperatures and pH. Over the last century, global ocean surface temperatures have increased by 0.74°C and seawater pH has declined by 0.1 units, while global predictions for 2100 suggest oceans will experience a decline in pH by 0.3-0.5 units. Thus, ocean acidification (OA) is a growing cause for concern since it adversely affects marine organisms such as corals and calcareous marine invertebrates. Research focusing on the effect of climate change on marine life has grown tremendously over the last two decades, with an emphasis on molluscs such as mussels and oysters which are considered ideal proxies for measuring environmental change and the underlying molecular effects thereof. However, research on abalone in this arena has primarily focused on larvae and the physiological effects of OA on development and shell growth. The underlying molecular mechanisms involved in the Haliotis midae stress response to ocean acidification have largely remained unexplored. Thus, this study sought to elucidate the effect of OA on the haemocyte proteome of H. midae, as well as to gain insight into the underlying molecular mechanisms that characterize the stress response of this abalone species. This study employed a comparative shotgun proteomics approach using isobaric tagging for relative and absolute quantification (iTRAQ) coupled with LC-MS/MS to investigate the proteomic response of H. midae haemocytes to reduced pH conditions representative of future predictions of ocean acidification. Four independent iTRAQ experiments were conducted where haemocytes were sampled after 12, 72 and 168 hours of exposure of H. midae to OA conditions (pH 7.5, represents OA predicted by 2100). Following quantitative analysis, 227 non-redundant and differentially expressed proteins were detected across the four independent experiments. Proteins of statistical significance (p ≤ 0.05) and biological relevance (foldchange ≥ 1.2) were identified. The 227 proteins were grouped according to their expression profile using Weighted Gene Cluster Network Analysis to gain an insight into the biological processes underlying the stress response of H. midae to OA conditions. Sequence similarity, Gene Ontology, data mining and network modelling based on other molluscs and well-characterised genomes were utilized for assigning putative functions to the grouped proteins. This revealed a multifaceted interplay of various biological processes and signaling pathways in H. midae, such as the induction of anaerobic metabolism, cytoskeletal stabilization and the induction of the ERK/MAPK signaling cascade. Notably, this analysis demonstrated a possible link between the stress and immune responses which has only been observed in other molluscs. Their complex association suggests an overlap of pathways, with putative dual functionality of proteins such as MAPK, CAMK, Serpin B2 and haemocyanin, all of which have been implicated in the stress and innate immune responses of other organisms. The combined data from the quantitative (Chapter 2) and functional analyses (Chapter 3) resulted in the compilation of a group of 33 candidate protein biomarkers of OA stress. A holistic and complete picture of the potential regulatory mechanisms involved in the stress response of H. midae was generated through protein-protein interaction network modelling and data mining. Aquarium-based experiments were conducted to validate the candidate OA biomarker proteins, as well as a set of previously identified biomarker candidates of acute temperature stress in H. midae (Calder and Coyne, unpublished), using label-free protein quantification (LFQ) coupled to LC-MS/MS analysis. Furthermore, the effect of a combination of reduced pH and elevated temperature on the candidate biomarker proteins was investigated. Five candidate biomarker proteins of OA stress were validated, while 10 candidates of acute temperature stress were detected and validated. The combined stress condition identified 7 potential biomarkers. Candidate biomarkers of OA stress were predominantly associated with the innate immune system, while those responding to temperature stress were largely associated with energetics and oxidative stress. Potential biomarkers of the combined stressors were found to be associated with signal transduction and intracellular trafficking. This component of the research project not only highlighted the importance of validation in biomarker discovery, but demonstrated the usefulness of an LFQ-proteomics approach for biomarker validation. This is the first time high-throughput shotgun proteomics has been employed to investigate the H. midae haemocyte stress response. This study provides a solid foundation for elucidating the putative functional stress response of a non-model organism, and highlights the complex dynamics and interplay between the stress and immune responses of H. midae. On-farm experimentation will be conducted to test whether the candidate biomarkers identified in this project can reliably detect abiotically stressed H. midae and whether they can be integrated into a “suite” of biomarkers for a health monitoring program for farmed H. midae. Successful implementation of such a health monitoring program will ensure the future sustainability of the South African abalone aquaculture industry despite the severity of climate change.